Expression of LamB Vaccine Antigen in Wolffia globosa (Duck Weed) Against Fish Vibriosis - Heenatigala, P. P. M.; Sun, Zuoliang; Yang, Jingjing; Zhao, Xuyao; Hou, Hongwei (Frontiers in Immunology, 2020)
Vibriosis is a commonly found bacterial disease identified among fish and shellfish cultured in saline waters. A multitude of Vibrio species has been identified as the causative agents. LamB, a member of outer membrane protein (OMPs) family of these bacteria is conserved among all Vibrio species and has been identified as an efficient vaccine candidate against vibriosis. Rootless duckweed (Wolffia) is a tiny, edible aquatic plant possessing characteristics suitable for the utilization as a bioreactor. Thus, we attempted to express a protective edible vaccine antigen against fish vibriosis in nuclear-transformed Wolffia. We amplified LamB gene from virulent Vibrio alginolyticus and it was modified to maximize the protein expression level and translocate the protein to the endoplasmic reticulum (ER) in plants. It was cloned into binary vector pMYC under the control of CaMV 35S promoter and introduced into Wolffia globosa by Agrobacterium-mediated transformation. Integration and expression of the LamB gene was confirmed by genomic PCR and RT-PCR. Western blot analysis revealed accumulation of the LamB protein in 8 transgenic lines. The cross-protective property of transgenic Wolffia was evaluated by orally vaccinating zebrafish through feeding fresh transgenic Wolffia and subsequently challenging with virulent V. alginolyticus. High relative percent survival (RPS) of the vaccinated fish (63.3%) confirmed that fish immunized with transgenic Wolffia were well protected from Vibrio infection. These findings suggest that Wolffia expressed LamB could serve as an edible plant-based candidate vaccine model for fish vibriosis and feasibility of utilizing Wolffia as bioreactor to produce edible vaccines.